Vision After Early-Onset Lesions of the Occipital Cortex: II. Physiological Studies - M. G. Knyazeva; P. Maeder; D. C. Kiper; T. Deonna; G. M. Innocenti (Neural Plasticity)
In one of two patients (MS and FJ) with bilateral, early-onset lesion of the primary visual cortex, Kiper et al. (2002) observed a considerable degree of functional recovery. To clarify the physiological mechanisms involved in the recovery, we used fMRI and quantitative EEG to study both patients. The fMRI investigations indicated that in both patients, isolated islands of the primary visual cortex are functioning, in the right hemisphere in MS and in the left in FJ. The functional recovery observed in MS roughly correlated with the functional maturation of interhemispheric connections and might reflect the role of corticocortical connectivity in visual perception. The functionality of interhemispheric connections was assessed by analyzing the changes in occipital inter-hemispheric coherence of EEG signals (ICoh) evoked by moving gratings. In the patient MS, this ICoh response was present at 7:11 y and was more mature at 9:2 y. In the more visually mpaired patient, FJ, a consistent increase in ICoh to visual stimuli could not be obtained, possibly because of the later occurrence of the lesion.